Development of glutamic acid decarboxylase immunoreactivity in the cat's lateral geniculate nucleus - Shotwell, SL (J Neurosci, 1986)
The development of glutamic acid decarboxylase (GAD) immunoreactivity in the cat's dorsal LGN was studied during fetal and postnatal life. In the adult, inhibitory interactions within the LGN are known to be mediated by GABA. Here we have used an antiserum to GAD, the rate- limiting synthetic enzyme for GABA, to examine the development of the anatomical substrate for this inhibitory system. The pattern of immunostaining observed in the adult cat LGN was similar to that reported by Fitzpatrick et al. (1984), with heavily stained somata and proximal dendrites located within the LGN layers and the adjacent perigeniculate nucleus (PGN). The LGN also contained a complex array of terminal staining. In development, specific staining was seen about 2 weeks before birth and was confined to PGN somata and, to a lesser extent, to somata located in the future ventral C-layers. A similar pattern of immunostaining was seen using GABA antiserum. Not until birth did the A-layers of the LGN show appreciable staining of both somata and terminals; however, even then the pattern of immunostaining was far from mature. Furthermore, excessive numbers of PGN neurons appeared to stain. By 5 weeks after birth, the intensity of both soma and terminal staining within the A-layers of the LGN increased substantially relative to that of the PGN and ventral C-layers. The first glomerular clusters of terminal staining could also be seen, and the number of stained PGN neurons had diminished to levels similar to those seen in the adult. The pattern of immunostaining was almost adultlike by 2 months after birth, except within the C-complex, where the staining did not yet show the distinct difference in staining intensity present in the adult between dorsal layer C and ventral layers C1 and C2. The final adult pattern of GAD immunoreactivity appeared by 3 months after birth. These results suggest that during fetal life the PGN and ventral C-layers of the LGN may supply the first source of GABA-mediated inhibition to the nucleus, with the major portion of the inhibition supplied by intrinsic LGN neurons arising postnatally. Thus, PGN neurons may provide part of the anatomical substrate for the inhibitory interactions seen physiologically during late fetal development (Shatz and Kirkwood, 1984). Finally, the relatively late appearance of the adultlike pattern of GAD immunostaining suggests that intrageniculate inhibitory circuitry continues to develop well after birth.